2010
DOI: 10.1371/journal.pbio.1000286
|View full text |Cite
|
Sign up to set email alerts
|

CDC5 Inhibits the Hyperphosphorylation of the Checkpoint Kinase Rad53, Leading to Checkpoint Adaptation

Abstract: The mechanistic role of the yeast kinase CDC5, in allowing cells to adapt to the presence of irreparable DNA damage and continue to divide, is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 68 publications
8
83
0
Order By: Relevance
“…In light of this, it is interesting to note that the CDC5 gene is not haploinsufficient for normal cell proliferation in yeast, which suggests that a 50 % reduction in the levels of this kinase is insufficient to delay cell cycle progression in the absence of DNA damage. In contrast, it has been shown that heterozygous mutations in CDC5 can affect the adaptation response, which suggests that the process responds quantitatively to Cdc5 activity in cells (Vidanes et al 2010). It is however conceivable that a change in Cdc5 substrate specificity might also be important for the initiation of the adaptation response.…”
Section: Polo-like Kinasesmentioning
confidence: 97%
See 4 more Smart Citations
“…In light of this, it is interesting to note that the CDC5 gene is not haploinsufficient for normal cell proliferation in yeast, which suggests that a 50 % reduction in the levels of this kinase is insufficient to delay cell cycle progression in the absence of DNA damage. In contrast, it has been shown that heterozygous mutations in CDC5 can affect the adaptation response, which suggests that the process responds quantitatively to Cdc5 activity in cells (Vidanes et al 2010). It is however conceivable that a change in Cdc5 substrate specificity might also be important for the initiation of the adaptation response.…”
Section: Polo-like Kinasesmentioning
confidence: 97%
“…It is difficult to determine whether the phosphatases that normally inactivate Rad53 during checkpoint recovery, PP2C and PP4 (Guillemain et al 2007;Leroy et al 2003;O'Neill et al 2007), are also involved in adaptation since mutants in these proteins are defective in both processes. Interestingly, it has been suggested that inactivation of Rad53 during adaptation could be mediated by Cdc5 phosphorylation-induced inhibition of Rad53 (Schleker et al 2010;Vidanes et al 2010) (Fig. 1c).…”
Section: Polo-like Kinasesmentioning
confidence: 97%
See 3 more Smart Citations